Daily field checking list by Walter Rosene, February 28, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Bob Walker, February 28, 1937. Also notes the Great Horned Owl was sitting on her two eggs. Her mate was being mobbed by a gang of American Crows a short distance away. Plustek--flatbed